Imbalance of Hsp70 family variants fosters tau accumulation - Jinwal, Umesh K. (Federation of American Societies for Experimental Biology, 2013)
Dysfunctional tau accumulation is a major contributing factor in tauopathies, and the heat-shock protein 70 (Hsp70) seems to play an important role in this accumulation. Several reports suggest that Hsp70 proteins can cause tau degradation to be accelerated or slowed, but how these opposing activities are controlled is unclear. Here we demonstrate that highly homologous variants in the Hsp70 family can have opposing effects on tau clearance kinetics. When overexpressed in a tetracycline (Tet)-based protein chase model, constitutive heat shock cognate 70 (Hsc70) and inducible Hsp72 slowed or accelerated tau clearance, respectively. Tau synergized with Hsc70, but not Hsp72, to promote microtubule assembly at nearly twice the rate of either Hsp70 homologue in reconstituted, ATP-regenerating Xenopus extracts supplemented with rhodamine-labeled tubulin and human recombinant Hsp72 and Hsc70. Nuclear magnetic resonance spectroscopy with human recombinant protein revealed that Hsp72 had greater affinity for tau than Hsc70 (I/I(0) ratio difference of 0.3), but Hsc70 was 30 times more abundant than Hsp72 in human and mouse brain tissue. This indicates that the predominant Hsp70 variant in the brain is Hsc70, suggesting that the brain environment primarily supports slower tau clearance. Despite its capacity to clear tau, Hsp72 was not induced in the Alzheimer's disease brain, suggesting a mechanism for age-associated onset of the disease. Through the use of chimeras that blended the domains of Hsp72 and Hsc70, we determined that the reason for these differences between Hsc70 and Hsp72 with regard to tau clearance kinetics lies within their C-terminal domains, which are essential for their interactions with substrates and cochaperones. Hsp72 but not Hsc70 in the presence of tau was able to recruit the cochaperone ubiquitin ligase CHIP, which is known to facilitate the ubiquitination of tau, describing a possible mechanism of how the C-termini of these homologous Hsp70 variants can differentially regulate tau triage. Thus, efforts to promote Hsp72 expression and inhibit Hsc70 could be therapeutically relevant for tauopathies.—Jinwal, U. K., Akoury, E., Abisambra, J. F., O'Leary, J. C., III, Thompson, A. D., Blair, L. J., Jin, Y., Bacon, J., Nordhues, B. A., Cockman, M., Zhang, J., Li, P., Zhang, B., Borysov, S., Uversky, V. N., Biernat, J., Mandelkow, E., Gestwicki, J. E., Zweckstetter, M., Dickey, C. A. Imbalance of Hsp70 family variants fosters tau accumulation.